2022
DOI: 10.3389/fmech.2022.900316
|View full text |Cite
|
Sign up to set email alerts
|

An analytical approach to entropy production in MHD mixed convection micropolar fluid flow over an inclined porous stretching sheet

Abstract: This analytical analysis examines the MHD micropolar fluid flow and mixed convection features using entropy production analysis of an inclined porous stretching sheet. Flow field and heat transfer analysis are presented to consider thermal radiation, heat source/sink, Lorentz, and buoyancy forces. The PDEs system is transformed by appropriate similarity variables, turned into a system of high non-linearity coupling ODEs, and then solved with the help of an analytical approach. An analytical approach can provid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 75 publications
0
1
0
Order By: Relevance
“…The study revealed that CuO nanoparticles increase heat transfer more than Al 2 O 3 , and were able to investigate the effect of a hybrid nanofluid on the heat sink. Sadighi et al (2022b) analytically solved the MHD micropolar fluid flow and mixed convection characteristics using entropy production analysis of a sheet that is stretched with an inclined porous surface. Jalili et al (2023d) carried out a numerical investigation of the magnetic field effect on the thermal behavior Frontiers in Mechanical Engineering frontiersin.org of a microchannel heat sink.…”
Section: Introductionmentioning
confidence: 99%
“…The study revealed that CuO nanoparticles increase heat transfer more than Al 2 O 3 , and were able to investigate the effect of a hybrid nanofluid on the heat sink. Sadighi et al (2022b) analytically solved the MHD micropolar fluid flow and mixed convection characteristics using entropy production analysis of a sheet that is stretched with an inclined porous surface. Jalili et al (2023d) carried out a numerical investigation of the magnetic field effect on the thermal behavior Frontiers in Mechanical Engineering frontiersin.org of a microchannel heat sink.…”
Section: Introductionmentioning
confidence: 99%